2013
DOI: 10.2139/ssrn.2244695
|View full text |Cite
|
Sign up to set email alerts
|

Disengagement: A Partial Solution to the Annuity Puzzle

Abstract: This research studies whether individuals make choices consistent with expected utility maximization in allocating wealth between a lifetime annuity and a phased withdrawal account at retirement. The paper describes the construction and administration of a discrete choice experiment to 854 respondents approaching retirement. The experiment finds overall rates of inconsistency with the predictions of the standard CRRA utility model of roughly 50%, and variation in consistency rates depending on the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…First, recent evidence shows that people have little knowledge about superannuation (Bateman et al ., ). There is a limited awareness among the working population of the ability to make salary sacrifice contributions and the associated tax implications.…”
Section: Discussionmentioning
confidence: 99%
“…First, recent evidence shows that people have little knowledge about superannuation (Bateman et al ., ). There is a limited awareness among the working population of the ability to make salary sacrifice contributions and the associated tax implications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to Cappelletti et al (2013), immediate life annuity demand is significantly lower for individuals with inferior financial literacy with respect to especially two proxies, namely knowledge of inflation and pension benefits (as cited in De Villiers-Strijdom 2021). Also, Bateman et al (2013) found that people with higher AIP awareness are more engaged with the retirement allocation decision-making process, and thus better equipped to manage longevity risk (as cited by De Villiers-Strijdom 2021).…”
Section: Annuity Puzzlementioning
confidence: 96%
“…For example, according to Cappelletti et al (2013), immediate life annuity demand is significantly lower for individuals with inferior financial literacy with respect to especially two proxies, namely knowledge of inflation and pension benefits (as cited in De Villiers-Strijdom 2021). Also, Bateman et al (2013) found that people with higher AIP awareness are more engaged with the retirement allocation decision-making process, and thus better equipped to manage longevity risk (as cited by De Villiers-Strijdom 2021).…”
Section: Annuity Puzzlementioning
confidence: 96%